Sensor Enabled Wearable Technological Tool to Detect Breast Abnormality - Kavitha, M; Venkata Krishna, P (International Journal of Engineering and Technology, 2018)
Our Historical records say that, Women are back bone to every family. Generally we observe that health risk rate in women increases depends on age. Statistical medical reports proven that, early identification of health risks will increase the survival rate of patient. From last sixty years, we heard that breast cancer is one of the big health dare for women after forty years of age. Early phase detection of breast tumor is a big research issue in both developed and developing countries. Due to the limits in existing breast abnormality detecting tools like mammography, thermography, ultrasound, MRI there is a need to introduce smart, cost effective, patient comfortable, non-ionic radiated compact testing tool to detect breast abnormality at early stage. In this work I am going to propose an advanced sensor enabled wearable technological tool design to detect breast abnormality. This tool is portable, patient comfortable, light weight, cost effective and suitable for dense breast, pregnant women and surgically altered breasts, younger women also.Â